Retinal visual processing constrains human ocular following response - Sheliga, B. M. (2013)
Ocular following responses (OFRs) are the initial tracking eye movements elicited at ultra-short latency by sudden motion of a textured pattern. We wished to evaluate quantitatively the impact that subcortical stages of visual processing might have on the OFRs. In three experiments we recorded the OFRs of human subjects to brief horizontal motion of 1D vertical sine-wave gratings restricted to an elongated horizontal aperture. Gratings were composed of a variable number of abutting horizontal strips where alternate strips were in counterphase. In one of the experiments we also utilized gratings occupying a variable number of horizontal strips separated vertically by mean-luminance gaps. We modeled retinal center/surround receptive fields as a difference of two 2-D Gaussian functions. When the characteristics of such local filters were selected in accord with the known properties of primate retinal ganglion cells, a single-layer model was capable to quantitatively account for the observed changes in the OFR amplitude for stimuli composed of counterphase strips of different heights (Experiment 1), for a wide range of stimulus contrasts (Experiment 2) and spatial frequencies (Experiment 3). A similar model using oriented filters that resemble cortical simple cells was also able to account for these data. Since similar filters can be constructed from the linear summation of retinal filters, and these filters alone can explain the data, we conclude that retinal processing determines the response to these stimuli. Thus, with appropriately chosen stimuli, OFRs can be used to study visual spatial integration processes as early as in the retina.